PENGEMBANGAN MEDIA PEMBELAJARAN WEB GOOGLE SITES MATERI SISTEM STARTER KELAS XII TKRO SMK PIRI SLEMAN - Kholid, Abdul; Rabiman, Rabiman; Hadi, Samsul (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2025)
This study aims to develop web-based learning media using the Google Sites platform for starter system materials while testing its feasibility. The method used is Research and Development (R&D) using the 4-D model according to Thiagarajan et al. (1974), including the stages of defining (define), designing (design), developing (develop), and disseminating (disseminate). The research subjects involved class XII students of Automotive Light Vehicle Engineering (TKRO) at SMK Piri Sleman. The feasibility of the media was assessed by material experts and media experts through a questionnaire instrument, while the data was analyzed descriptively quantitatively. The results show that the web-based learning media through Google Sites obtained a feasibility score of 95.00% according to material experts, 93.75% according to media experts, and 88.85% based on responses from 20 students, all of which are categorized as highly feasible. Compared to conventional offline media, this media is superior in accessibility, multimedia integration, and ease of content updates. These results demonstrate the potential of this media in increasing student engagement and supporting flexible independent learning.